Innovational Model for Cooperation Membership Development Through Human Resources Development - Dwi Astutiek (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
The model for fostering cooperative members has so far been limited to general and ceremonial matters, which is not sustainable, resulting in the cooperative becoming ill and possibly collapsing. For the development of cooperative members so that they can give meaning and be carried out in a sustainable manner, an innovation model is needed in coaching through the concept of human resource development. The purpose of this study is first, to describe the innovative model of fostering cooperative members. Second, to answer the question of survival in relation to family economic independence in an era of uncertainty. This type of research uses a qualitative descriptive approach. Data collection techniques were carried out by means of observation, in-depth interviews, and documentation of references and photos/videos. Data were obtained from several informants whose number was not determined beforehand, by appointing one key informant. Members of cooperatives whose postscript are MSME actors. It is necessary to strengthen survival from an uncertain era, namely by involving members to organize their hearts, mapping their own potential, conducting market mapping, having strong faith in doing business and surrendering to the giver of fortune, expanding relationships, building an entrepreneurial spirit by continuing to innovate in life and always be grateful for destiny to be Happy (7M).The results showed that there was an increase in the productivity of cooperative members from the 7M coaching innovation model approach.